2021
DOI: 10.1101/2020.12.30.20248929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antemortem vs. postmortem histopathological and ultrastructural findings in paired transbronchial biopsies and lung autopsy samples from three patients with confirmed SARS-CoV-2 infection

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is the major cause of death in coronavirus disease 2019 (COVID-19). Multiple autopsy-based reports of COVID-19 lung pathology describe diffuse alveolar damage (DAD), organizing pneumonia (OP) and fibrotic change, but data on early pathological changes as well as during progression of the disease are rare.Research questionComparison of histopathological and ultrastructural findings in paired transbronchial biopsies (TBBs) and autopsy material from three patie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The copyright holder for this this version posted November 30, 2022. ; https://doi.org/10.1101/2022.11.29.22282913 doi: medRxiv preprint from the presence of virus [15]. With respect to autoantibodies, 33.3% of patients in the present study had detectable autoantibodies (ANA/ENA).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The copyright holder for this this version posted November 30, 2022. ; https://doi.org/10.1101/2022.11.29.22282913 doi: medRxiv preprint from the presence of virus [15]. With respect to autoantibodies, 33.3% of patients in the present study had detectable autoantibodies (ANA/ENA).…”
Section: Discussionmentioning
confidence: 61%
“…The proportion of CD163+ macrophage subpopulation in PASC lung tissue samples was higher than in a previously published control cohort, but this result was not statistically significant and the density of pro-fibrotic macrophages did not correlate with presence of fibrosis, clinical or imaging characteristics or the detection of autoantibodies. Still, we feel that pulmonary function should be monitored closely in PASC patients to allow for early detection and treatment of possible pulmonary fibrosis since it has been previously shown that SARS-CoV-2 has the ability to induce lung fibrosis [30,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-mortem investigation, i.e., autopsy, provides a comprehensive insight into the pathophysiology of novel diseases such as COVID-19, allowing investigation of the multisystemic viral spread and effects on a tissue and cellular level [8]. Recent studies using in situ hybridization (ISH) have found SARS-CoV-2 tropism and replication in airways, i.e., trachea, lung, bronchi, or submucosal glands, within pneumocytes, alveolar and pulmonary lymph node macrophages, endothelium, and respiratory epithelium [9][10][11][12][13][14][15][16]. In the extra-respiratory organs, ISH demonstrated direct infection of vascular endothelium in the kidney (renal proximal and distal tubular epithelial cells) [14,[17][18][19], heart [15], liver [14], brain stem and leptomeninges [14] and placenta (syncytiotrophoblast and cytotrophoblast) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Post-mortem investigation, i.e., autopsy, provides a comprehensive insight into the pathophysiology of novel diseases, such as COVID-19, allowing investigation of the multisystemic viral spread and effects on a tissue and cellular level 3 . Recent studies using in situ hybridization (ISH) have found SARS-CoV-2 tropism and replication in airways, i.e., trachea, lung, bronchi, or submucosal glands, within pneumocytes, alveolar and pulmonary lymph node macrophages, endothelium, and respiratory epithelium [4][5][6][7][8][9][10][11] . In extra-respiratory organs, ISH demonstrated direct infection of vascular endothelium in the kidney (renal proximal and distal tubular epithelial cells) 9,12-14 , heart 10 , liver 9 , brain stem and leptomeninges 9 and placenta (syncytiotrophoblast and cytotrophoblast) 15 .…”
Section: Introductionmentioning
confidence: 99%